Predicting the current and future global distribution of the invasive freshwater hydrozoan Craspedacusta sowerbii - Guillaume Marchessaux (Nature Portfolio, 2021)
Abstract The freshwater jellyfish Craspedacusta sowerbii is one of the most widespread invasive species, but its global distribution remains uncertain due to ephemeral appearances and general lack of information in various aquatic environments. The aim of this study was to map current and future distributions (2050 and 2100) using Species Distribution Models allowing to visualize the habitat suitability and make projections of its changes under potential climate change scenarios. Except in Oceania where the range decreased, an expansion of C. sowerbii was projected during the next century under modeled future scenarios being most intensive during the first half of the century. The present study shows that the expansion of C. sowerbii worldwide would be facilitated mainly by precipitation, vapor pressure, and temperature. The predictions showed that this species over the eighty years will invade high-latitude regions in both hemispheres with ecological consequences in already threatened freshwater ecosystems.